The economic organization - Knight, Frank H. (Augustus M. Kelley, 1967)
“The Economic Organization” provides a short introduction to the basic principles of supply, demand, and distribution that emerge from neoclassical price theory. The central role of the price mechanism in market organization is illustrated neatly by Knight’s "wheel of wealth"—the circular flow diagram most often identified with macroeconomic flows, but introduced here for price theoretic reasons.